2009
DOI: 10.1203/pdr.0b013e3181b3b110
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Recovery Is as Fast With Air Ventilation as With 100% Oxygen After Asphyxia-Induced Cardiac Arrest in Piglets

Abstract: ABSTRACT:We investigated return of spontaneous circulation and of cerebral oxygenation after asphyxia-induced cardiac arrest, using ventilation with air, throughout, or with 100% oxygen for a shorter or longer period. Arterial pressure, heart rate, regional cerebral oxygen saturation (CrS O2 ), and brain tissue oxygen tension (Pbt O2 ) were measured in 1-d-old piglets that were hypoventilated with air and left in apnea until cardiac arrest. They were randomly assigned to be resuscitated with air (n ϭ 13), or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 12 publications
1
35
0
1
Order By: Relevance
“…[216][217][218][219][220][221][222][223] 222 One demonstrated more rapid restoration of cerebral blood flow but no difference in histologic brain injury scores. 224 For the critical outcome of oxidative injury, we found 10 animal studies reported on oxidative injury with varying results 212,213,216,[219][220][221][222][223][225][226][227] (very-low-quality evidence, downgraded for potential bias, inconsistency, and indirectness).…”
Section: Consensus On Sciencementioning
confidence: 95%
See 1 more Smart Citation
“…[216][217][218][219][220][221][222][223] 222 One demonstrated more rapid restoration of cerebral blood flow but no difference in histologic brain injury scores. 224 For the critical outcome of oxidative injury, we found 10 animal studies reported on oxidative injury with varying results 212,213,216,[219][220][221][222][223][225][226][227] (very-low-quality evidence, downgraded for potential bias, inconsistency, and indirectness).…”
Section: Consensus On Sciencementioning
confidence: 95%
“…For the critical outcome of ROSC, we found 8 animal studies (lambs/pigs/ rats) [216][217][218][219][220][221][222][223] all demonstrating no advantage to 100% over 21% during CPR (very-low-quality evidence, downgraded for bias and indirectness).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Animal evidence shows no advantage to 100% oxygen during CPR. [179][180][181][182][183][184][185][186] However, by the time resuscitation of a newborn infant has reached the stage of chest compressions, efforts to achieve return of spontaneous circulation using effective ventilation with low-concentration oxygen should have been attempted. Thus, it would appear sensible to try increasing the supplementary oxygen concentration.…”
Section: It Ismentioning
confidence: 99%
“…Evidence from animal studies shows that supplemental oxygen during resuscitation causes significant hyperoxia in the newborn brain (16,17), with increased generation of reactive oxygen species (18), oxidative stress (19), inflammation (20), and cerebral injury (19,21,22). Clinical studies have shown that resuscitation with 100% oxygen has no advantage over air but causes increased mortality (23) and increased time to first breath and/ or cry (24)(25)(26).…”
mentioning
confidence: 99%